2006
DOI: 10.1185/030079906x148418
|View full text |Cite
|
Sign up to set email alerts
|

Comparing bimatoprost and travoprost in black Americans

Abstract: Bimatoprost and travoprost each effectively lowered IOP in this population of black patients. More patients achieved clinically relevant IOP reductions with bimatoprost.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2010
2010
2012
2012

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 10 publications
0
16
0
1
Order By: Relevance
“…2,3 Conversely, travoprost has been shown to be more effective in black patients than in Caucasians in some studies. 7 However, Noecker et al 10,11 compared bimatoprost with travoprost in African Americans with glaucoma or ocular hypertension (OHT), and found that bimatoprost was more likely than travoprost to achieve target pressure at 3 months.…”
Section: Introductionmentioning
confidence: 98%
“…2,3 Conversely, travoprost has been shown to be more effective in black patients than in Caucasians in some studies. 7 However, Noecker et al 10,11 compared bimatoprost with travoprost in African Americans with glaucoma or ocular hypertension (OHT), and found that bimatoprost was more likely than travoprost to achieve target pressure at 3 months.…”
Section: Introductionmentioning
confidence: 98%
“…After looking through a large collection of papers of clinical trials on IOP reductions and on comparing drugs for type-2 diabetes, we believe that the above three categories cover a significant proportion of statistical information (e.g., [4,7,15,21,30,32,34,37,40], etc).…”
Section: Obtaining Sampling Distributions From Clinical Trialsmentioning
confidence: 99%
“…A huge number of clinical trials have been carried out in the last few decades and new trials are constantly being designed and implemented. For example, many clinical trials have been carried out to investigate issues including: the intraocular pressure (IOP) lowering efficacy of drugs, such as travoprost, bimatoprost, timolol, and latanoprost, (e.g., [4,7,15,21,30,32,34,37,40]); oral medications for adults with Type-2 diabetes (e.g., [3,9,27,29,35,41]); the neurocognitive outcomes after off-pump versus on-pump coronary revascularisation (e.g., [14,25,26,31,43]). …”
Section: Introductionmentioning
confidence: 99%
“…Bimatoprost was superior in IOP lowering to travoprost only during the daytime (0800 and 1200 hours time-points), but latanoprost and travoprost were comparable at all time points (P # 0.82). 88 An industry-sponsored meta-analysis 90 of travoprost vs latanoprost (15 trials, n = 1098), 57,68,85,93,95,96,[98][99][100] travoprost vs bimatoprost (8 trials, n = 714), 57,85,87,93,95,96,101,102 and latanoprost vs bimatoprost (8 trials, n = 943) 57,64,85,86,93,95,96,103 found similar efficacy among the three PGAs. Studies comparing the PGA to other non-PGA glaucoma treatments, nonrandomized, dose-finding or cross-over trials, and short-term evaluations (less than 3 months) were excluded, although a trial evaluating timolol plus travoprost versus timolol alone, 100 was included indicating that the PGA effect has the same relative effect as if it were compared with no treatment.…”
mentioning
confidence: 99%